Differences between adult and pediatric onset Henoch‐Schonlein purpura from North India. (8th November 2017) - Gupta, Vikas; Aggarwal, Amita; Gupta, Ranjan; Chandra Chowdhury, Abhra; Agarwal, Vikas; Lawrence, Able; Misra, Ramnath
Abstract: Aim: Henoch‐Schönlein purpura (HSP), a primary vasculitis, characterized by purpura, abdominal pain, arthritis and renal involvement, is predominantly a disease of childhood. However, rarely it can occur in adults in whom it is believed to be a more severe form with poor renal outcomes. We aimed to answer if the age of onset affected the clinical spectrum and renal outcomes of the disease in a north Indian population. Hence, we studied the differences in clinical spectrum and renal outcomes between adult‐onset HSP and childhood‐onset HSP. Methods: Case records of all adult patients diagnosed with HSP (onset ≥ 18 years) over the last 25 years in our department (1992–2017) were retrieved. Data on clinical features, lab abnormalities and outcomes were extracted and compared with that in pediatric HSP patients (onset < 18 years) seen during the same period. Results: A total of 87 patients, including 30 adults and 57 children, were seen during this period. Compared to children, most of the adults had purpura as the first clinical manifestation (86.7% vs . 56.1%, P < 0.01) whereas abdominal pain was only rarely the initial symptom in adults (10.0% vs . 36.8%, P < 0.02). During the disease course, adults had a higher frequency of joint involvement as compared to children (90.0% vs . 43.9%, P < 0.001). There was no significant difference in the frequency of renal involvement (60.0% vs . 50.9%, P = NS) and gastrointestinal involvement (66.7% vs . 84.2%, P = NS) between adults and children. Outcomes were good in both groups and most adults and children achieved complete recovery (83.3% and 86.0%, respectively). There was no difference in the frequency of immunosuppressive treatment required by the two groups. None of the patients developed renal insufficiency on follow‐up. Conclusion: Compared to children, adults with HSP seldom have abdominal pain as the first clinical manifestation while joint involvement is seen more commonly in them during the disease course.